Distribution and Function of the Bestrophin-1 (Best1) Channel in the Brain - Oh, Soo-Jin; Lee, C. Justin (KOREAN SOC BRAIN & NEURAL SCIENCE, KOREAN SOC NEURODEGENERATIVE DISEASE, 2017)
Bestrophin-1 (Best1) is a calcium-activated anion channel identified from retinal pigment epithelium where human mutations are associated with Best's macular degeneration. Best1 is known to be expressed in a variety of tissues including the brain, and is thought to be involved in many physiological processes. This review focuses on the current state of knowledge on aspects of expression and function of Best1 in the brain. Best1 protein is observed in cortical and hippocampal astrocytes, in cerebellar Bergmann glia and lamellar astrocytes, in thalamic reticular neurons, in meninges and in the epithelial cells of the choroid plexus. The most prominent feature of Best1 is its significant permeability to glutamate and GABA in addition to chloride ions because glutamate and GABA are important transmitters in the brain. Under physiological conditions, both Best1-mediated glutamate release and tonic GABA release from astrocytes modulate neuronal excitability, synaptic transmission and synaptic plasticity. Under pathological conditions such as neuroinflammation and neurodegeneration, reactive astrocytes phenotypically switch from GABA-negative to GABA-producing and redistribute Best1 from the perisynaptic microdomains to the soma and processes to tonically release GABA via Best1. This implicates that tonic GABA release from reactive astrocyte via redistributed Best1 is a common phenomenon that occur in various pathological conditions with astrogliosis such as traumatic brain injury, neuroinflammation, neurodegeneration, and hypoxic and ischemic insults. These properties of Best1, including the permeation and release of glutamate and GABA and its redistribution in reactive astrocytes, promise us exciting discoveries of novel brain functions to be uncovered in the future.
Keywords: CL-CHANNELS; ASTROCYTES; GENE; GABA; IDENTIFICATION; CONDUCTANCE; EXPRESSION; MEMBRANE; RELEASE; PROTEIN